(untitled) (Veterinary Science, 2017)
he possible utilization of PCR as a diagnostic tool for enzootic bovine leukosis, comparing its use to traditional serologic techniques such as immunodiffusion agar assay (IDGA) and enzyme-linked immunoabsorbent assay (ELISA) under epidemiological conditions present in Argentina, is analized. Further the use of alternative strategies associated with PCR will be reviewed in order to evaluate the use of PCR as a routine technique in modrately sophisticated laboratories. It is concluded that PCR becomes important under situaations of low prevalence, in cases where it becomes necessary to define specific epidemiological circunstances